Effect of the family medicine approach in reducing stunting among toddlers - Werdhani, Retno Asti; Koloi, Vican Sefiany; Tantri, Julietta; Mahardika, Abiyyu Ghiyats; Widjaja, Lydia Rosalina; Michelle, Michelle; Tiffany, Tiffany (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundOne health indicator assessed for achieving the Sustainable Development Goals (SDGs) is the nutritional status of toddlers. Stunting, indicating chronic malnutrition in children, remains a pressing concern globally, especially in low‑ and middle‑income countries. Stunting is still prevalent in Jakarta as the capital city of Indonesia. The study's objective was to evaluate the implementation of the family medicine approach on stunting in toddlers in Koja Sub-District, North Jakarta. MethodsA pre- and post-test design study was conducted involving 40 toddlers who were diagnosed with stunting. Outcome variables were body weight, height, and stunting while the independent variable was the family medicine approach (home visits, family education, and monitoring for 3 months). The Friedman test was used to determine the difference in height and weight after 3 months of the family medicine approach. ResultsAfter 3 months of the family medicine approach, consisting of holistic history taking, performing a thorough physical examination, educating parents about toddlers' nutritional issues, and conducting routine monthly home visits, the toddlers’ body weight increased by 0.68 kg and their height increased by 1.37 cm (p<0.001). The total number of cases of stunting after the family medicine approach decreased by 30% (12/40) from 40 to 28. ConclusionsThere is a decrease in the number of stunting cases after the family medicine approach, but further research is needed. The study findings will help to improve policy measures focusing on the family medicine approach to reduce childhood stunting.